Intervention and Acceptance Rates Support Handshake-Stewardship Strategy. (15th June 2018) - Hurst, Amanda L; Child, Jason; Parker, Sarah K
Abstract: We instituted a new antimicrobial stewardship approach that involves review of all antimicrobial agents and communication of interventions in person by a pharmacist–physician team termed handshake stewardship. The acceptance rate in this study was 86%, intervention rates were higher with a physician, and interventions on antibiotics not reviewed by other strategies were made frequently.